Communication process of adolescent children and their OFW parent - Herrera, Nhiga A.
This study aimed to describe elements of the communication process and the perception of problems and changes in the communication patterns of adolescents and their Overseas Filipino Worker (OFW) parent. Respondents were 86 first to fourth year students of Pampanga High School selected through purposive sampling. They were given a set of self-administered questionnaires composed of socio-demographic profiles of the adolescents and their OFW parents, questions describing mode, frequency, length of communication, manner of making and receiving the calls, topics of conversation, and the perceived problem and changes in the communication patterns. The study showed that a large majority (77%) of OFW families used multiple modes of communication preferring channels with direct interaction such as phonecall (99%) and text messaging (69%). Phone calls, which were usually made by the OFW parents were done once a week with the call being shared with various members of the family. Conversations with the adolescents usually revolved around the education-related and money-related terms. Respondents reported a generally positive perception of their communication with their OFW parent. Problems encountered were mostly on the physical barriers such as phone signals, choppy lines and lack money for calling. Respondents perceived both positive and negative changes in their communication. The adolescents reported that their communication with parents abroad either become more frequent, open and deeper due to the excitement of talking to each other or seldom and shallow due to physical distance. They also exhibited a positive perception towards their parents working abroad and towards overseas employment in general.